Impact of Polycyclic Aromatic Hydrocarbon Accumulation on Oyster Health - Gan, Nin; Martin, Leisha; Xu, Wei (Frontiers in Physiology, 2021)
In the past decade, the Deepwater Horizon oil spill triggered a spike in investigatory effort on the effects of crude oil chemicals, most notably polycyclic aromatic hydrocarbons (PAHs), on marine organisms and ecosystems. Oysters, susceptible to both waterborne and sediment-bound contaminants due to their filter-feeding and sessile nature, have become of great interest among scientists as both a bioindicator and model organism for research on environmental stressors. It has been shown in many parts of the world that PAHs readily bioaccumulate in the soft tissues of oysters. Subsequent experiments have highlighted the negative effects associated with exposure to PAHs including the upregulation of antioxidant and detoxifying gene transcripts and enzyme activities such as Superoxide dismutase, Cytochrome P450 enzymes, and Glutathione S-transferase, reduction in DNA integrity, increased infection prevalence and reduced and abnormal larval growth. Much of these effects could be attributed to either oxidative damage or a reallocation of energy away from critical biological processes such as reproduction and calcification towards health maintenance. Additional abiotic stressors including increased temperature, reduced salinity, and reduced pH may change how the oyster responds to environmental contaminants and may compound the negative effects of PAH exposure. The negative effects of acidification and longer-term salinity changes appear to add to that of PAH toxicity, while shorter-term salinity changes may induce mechanisms that reduce PAH exposure. Elevated temperatures, on the other hand, cause such large physiological effects on their own that additional PAH exposure either fails to cause any significant effects or that the effects have little discernable pattern. In this review, the oyster is recognized as a model organism for the study of negative anthropogenic impacts on the environment, and the effects of various environmental stressors on the oyster model are compared, while synergistic effects of these stressors to PAH exposure are considered. Lastly, the understudied effects of PAH photo-toxicity on oysters reveal drastic increases in the toxicity of PAHs via photooxidation and the formation of quinones. The consequences of the interaction between local and global environmental stressors thus provide a glimpse into the differential response to anthropogenic impacts across regions of the world.